Short-term fluxes of nitrous oxide from soil: measurement and modelling - Ashby, Conrad Philip (1996)
Gaseous nitrous oxide (N₂0) undergoes physical and chemical reactions in the atmosphere, contributing to both global warming and the catalytic destruction of stratospheric ozone. This chemically reactive greenhouse gas is produced both naturally and anthropogenically. The greatest source of N₂0 is from the microbial transformation of N compounds during the processes of nitrification and denitrification in natural and cultivated soils. However, there is some uncertainty in the strength of these emission sources. Therefore one of the directives of the Terrestrial Initiative in Global Environmental Research programme, of which the following work was a part, was to elucidate the factors which influence the emission rates of N₂0 from these systems. It is essential that these factors are quantified, in order to correctly assess the effect of N₂0 as an environmental determinant.